Las tecnologías de la información y comunicación TIC’s y su contribución en la producción de cultivos - Beltran Analuiza, Anthony Patricio (2020)
Technology goes hand in hand with agriculture, as the farmer looks for a way to facilitate the work he does in the field, such as plowing. The technology benefits agriculture in many ways, many of which aid in the early detection of disease or nutrient deficiency. With the help of technology it is possible to develop agriculture in urban areas, a clear example is the orchards that are made. The use of drones in agriculture progresses more every day, they are used more and more, since they capture high resolution images in real time of the presence of diseases, deficiency of some nutrient, presence of weeds, so the farmer can carry out its timely checks. GPS is used in some agricultural machines, such as combines and tractors. These instruments not only serve to know the location, but also detect the areas of the crop that have the highest incidence of weeds and diseases. GPS is also used for topographic plan surveys. The use of technologies is aimed at improving crop production, due to the improvements that can be made thanks to them. Thus same production costs go down because the farmer will not waste products but only apply the necessary amount.